Use of mesh in laparoscopic paraesophageal hernia repair: a meta-analysis and risk-benefit analysis - Müller, Beat P.; Kenngott, Hannes Götz; Stock, Christian; Linke, Georg R.; Fritz, Franziska; Nickel, Felix; Diener, Markus K.; Wente, Moritz N.; Büchler, Markus W.; Fischer, Lars (PLOS ONE, 2015)
Introduction Mesh augmentation seems to reduce recurrences following laparoscopic paraesophageal hernia repair (LPHR). However, there is an uncertain risk of mesh-associated complications. Risk-benefit analysis might solve the dilemma. Materials and Methods A systematic literature search was performed to identify randomized controlled trials (RCTs) and observational clinical studies (OCSs) comparing laparoscopic mesh-augmented hiatoplasty (LMAH) with laparoscopic mesh-free hiatoplasty (LH) with regard to recurrences and complications. Random effects meta-analyses were performed to determine potential benefits of LMAH. All data regarding LMAH were used to estimate risk of mesh-associated complications. Risk-benefit analysis was performed using a Markov Monte Carlo decision-analytic model. Results Meta-analysis of 3 RCTs and 9 OCSs including 915 patients revealed a significantly lower recurrence rate for LMAH compared to LH (pooled proportions, 12.1% vs. 20.5%; odds ratio (OR), 0.55; 95% confidence interval (CI), 0.34 to 0.89; p = 0.04). Complication rates were comparable in both groups (pooled proportions, 15.3% vs. 14.2%; OR, 1.02; 95% CI, 0.63 to 1.65; p = 0.94). The systematic review of LMAH data yielded a mesh-associated complication rate of 1.9% (41/2121; 95% CI, 1.3% to 2.5%) for those series reporting at least one mesh-associated complication. The Markov Monte Carlo decision-analytic model revealed a procedure-related mortality rate of 1.6% for LMAH and 1.8% for LH. Conclusions Mesh application should be considered for LPHR because it reduces recurrences at least in the mid-term. Overall procedure-related complications and mortality seem to not be increased despite of potential mesh-associated complications.
Gesehen am 05.08.2020